Effectiveness of Giving Ambon Banana, Avocado and Honey Juice on Increasing Hemoglobin (Hb) Levels in Pregnant Women - Retno Palupi Yonni Siwi; Erma Retnaningtyas; Anggrawati Wulandari; Nur Yeny Hidajaturrokhmah; Era Pebriana (Journal of Nursing Practice)
Background: Anemia in pregnancy is a condition in which the mother has a hemoglobin level below 11 gr% in the first and third trimesters, and a level below 10.5 gr% in the second trimester. Most anemia in pregnancy is caused by iron deficiency and acute bleeding.